COMPARATIVE STUDY OF HISTERETIC BEHAVIOR AND SEISMIC PERFORMANCE OF VARIOUS VISCOELASTIC DAMPER MODELS IN A MIDDLE-RISE BUILDING - Arsia Ikram Ramdani, Elga
Indonesia is one of the countries frequently struck by earthquakes due to its geographical location along the Ring of Fire. The impacts of these earthquakes are often highly destructive, resulting in significant loss of life and property. Therefore, earthquake-resistant structural design is crucial to mitigate the risks and losses caused by earthquakes. Currently, there is considerable potential for implementing modern earthquake-resistant structures that utilize various seismic energy dissipation devices such as dampers to absorb earthquake energy. To create an optimal modern earthquake-resistant structural design, accurate and representative structural modeling is essential. This research aims to study the behavior of viscoelastic dampers (VED) as components of modern earthquake-resistant systems. The research also aims to compare and determine the most representative model among various models available in ETABS for modeling VED. In this study, various VED models are evaluated at both the element and structural levels to understand their behavior and characteristics. The models to be compared include the Voigt Model, Plastic Wen Model, Multilinear Plastic Model, and 3 element model. The differences between these four models are based on variations in the configuration of springs and dashpots used in the models. Meanwhile, parameters for comparison among the models include delayed elasticity, frequency-dependent behavior, hysteresis curve, base shear, and the relationship between damping force and displacement in the structure. Numerical testing in ETABS is used to validate the VED models developed, and linear time history analysis is conducted using the Fast Nonlinear Analysis (FNA) method. The results of the research indicate that the 3 element model is the most representative for modeling VED behavior in the field.